2022
DOI: 10.1007/s00190-022-01647-4
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating error variance and scaling global covariance function of geoid gradients for optimal determinations of gravity anomaly and gravity gradient from altimetry

Abstract: With the advancements of satellite altimeter technology and data volume, the accuracy and spatial resolution of altimeter-derived marine gravity fields have been steadily improved. Ideally, a best marine gravity field from multi-altimeter missions is one that combines all data by optimally calibrating their relative weights. To this end, we use the minimum norm quadratic unbiased estimator theory to calibrate error variances of geoid gradients (GGs) from the Cryosat-2 mission and the Jason-1/2 geodetic mission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Yu and Hwang [26] derived the VGG based on altimetry data from the Cryosat-2 and Jason-1/2. Zhou et al [27] developed a vertical gravity anomaly gradient model with a resolution of 1 × 1 for the Arabian Sea and its surrounding regions from the altimetry data of Cryosat-2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu and Hwang [26] derived the VGG based on altimetry data from the Cryosat-2 and Jason-1/2. Zhou et al [27] developed a vertical gravity anomaly gradient model with a resolution of 1 × 1 for the Arabian Sea and its surrounding regions from the altimetry data of Cryosat-2.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the use of gravity gradients enhances the reliability of inversion of bathymetry and underwater gravity matching navigation [32][33][34][35]. However, most researchers primarily focus on computing VGG [26] using the derivation formula provided by Heiskanen and Moritz [36,37]. Wan et al [15] found that few methods have been proposed to invert full tensor of gravity gradients from altimetry data.…”
Section: Introductionmentioning
confidence: 99%